BILAC'S CHRONICLE IN THE BRUXA (1896-1897) - Simoes Junior, Alvaro Santos [UNESP] (Assoc Nac Pos-graduacao Pesquisa Letras & Linguistica, 2015)
Together with Portuguese illustrator Juliao Machado, Olavo Bilac directed the weekly periodical A Bruxa from February 1896 to June 1897. In this illustrated magazine, the Parnassian poet wrote the Cronica column, that was always published on the second page, embellished with Gothic vignettes by Machado. Through this weekly conversation with the carioca reader, Bilac strengthened the trend of Brazilian chronicle toward humor and irony and contributed to make the genre in Brazil much more literary expression of a subjetivity than a journalistic section merely intended to review the main week events.
Keywords: Olavo Bilac; Juliao Machado; A Bruxa; Chronicle; Press